Improving User Experience for the Web Platform Spotlight Heritage Timisoara with AI Technologies - Valentin Sorescu; Diana Andone (Ubiquity Proceedings)
By utilizing modern machine learning technologies and integrating the database of the Spotlight Heritage project, the virtual assistant is capable of providing precise and relevant responses to various user inquiries and requests. Its functionality includes specific searching within the site, offering results and personalized recommendations based on user preferences. Extensive testing with real users and the implementation of a continuous monitoring and updating script have contributed to the consolidation of the virtual assistant’s quality and effectiveness. Feedback received from users has been essential in continuously optimizing functionalities and improving the user experience. The virtual assistant represents not only a valuable resource for exploring the cultural heritage of Timisoara but also a tool for promoting and conserving local history and culture. I am proud to be part of the team that has contributed to the realization of this innovative project, which continues to inspire and educate the local community and visitors alike.